Armutsrisiko alleinerziehend Die Bedeutung von sozialer Komposition und institutionellem Kontext in Deutschland - Hübgen, Sabine (Verlag Barbara Budrich, 2020)
This book investigates the reasons for lone mothers' high poverty rates in Germany. It sheds some light on both the family and employment trajectories, and the institutional context. In quantitative analyses the poverty-enhancing effect of lone mothers' social composition and of lone motherhood per se is identified. The influence of the institutional context is quantified by means of a period and country comparison with the UK.